Characterization and antimicrobial resistance of clinical isolates of enterococci in tertiary care hospital in eastern Nepal - Nepal, Hari Prasad; Khanal, B; Acharya, A (Health Renaissance, 2013)
Health Renaissance, January-April 2013; Vol. 11 No.1; 17-22 DOI: http://dx.doi.org/10.3126/hren.v11i1.7595